2023
DOI: 10.2106/jbjs.22.00675
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Essential Amino Acid Supplementation Facilitates Quadriceps Muscle Strength and Volume Recovery After TKA

Abstract: Background: Perioperative essential amino acid (EAA) supplementation suppresses lower-limb muscle atrophy and promotes functional improvement in the first 4 weeks after total knee arthroplasty (TKA). However, its effect on the recovery of muscle volume and strength in the intermediate term is unclear. The aim of this study was to evaluate the effect of perioperative EAA supplementation on the recovery of lower-limb muscle volume and strength in the 2 years after TKA.Methods: Sixty patients who underwent unilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
2
13
1
Order By: Relevance
“…Studies evaluating EAA supplementation after TKA all demonstrated decreased muscle loss after surgery and improved recovery of functional mobility including rectus femoris muscle volume and quadriceps muscle strength up to 2 years after surgery. 10,15,18 In summary, literature supports the clinical efficacy of EAA supplementation in not just mitigating sarcopenia because of immobility and immobilization but also improved functional recovery postoperatively (Table 1).…”
Section: Essential Amino Acids and Their Role In Mitigating Sarcopeniamentioning
confidence: 86%
See 1 more Smart Citation
“…Studies evaluating EAA supplementation after TKA all demonstrated decreased muscle loss after surgery and improved recovery of functional mobility including rectus femoris muscle volume and quadriceps muscle strength up to 2 years after surgery. 10,15,18 In summary, literature supports the clinical efficacy of EAA supplementation in not just mitigating sarcopenia because of immobility and immobilization but also improved functional recovery postoperatively (Table 1).…”
Section: Essential Amino Acids and Their Role In Mitigating Sarcopeniamentioning
confidence: 86%
“…Studies evaluating EAA supplementation after TKA all demonstrated decreased muscle loss after surgery and improved recovery of functional mobility including rectus femoris muscle volume and quadriceps muscle strength up to 2 years after surgery. 10,15,18…”
Section: Essential Amino Acids and Their Role In Mitigating Sarcopeniamentioning
confidence: 99%
“…Since the accuracy of the bone cut is increasing owing to the development of the navigation and robot systems [15], such inter‐surgeon difference may have significant clinical relevance in robotic‐assisted TKAs. Because the medial flexion gap is a reliable indicator of soft‐tissue balancing and is associated with patient satisfaction and patient‐reported subjective scores after TKA [1, 16, 19], manual stress measurements in navigation and robot systems must be improved [4, 21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate soft‐tissue balancing is important in achieving a good clinical outcome, patient satisfaction, and a long‐term implant survival after total knee arthroplasty (TKA) [1, 3, 5, 11, 19]. Joint gap measurement is most commonly performed under static conditions, with the knee extended and performing a 90° flexion using a gap tensioner/spreader [18].…”
Section: Introductionmentioning
confidence: 99%
“…Another RCT showed no differences with regard to blood loss, thigh and knee pain, edema, and complications between patients who underwent the procedure without a tourniquet and those patients who had optimized use of it 19 . With regard to quadriceps muscle strength and volume recovery after TKA, a trial comparing perioperative essential amino acid supplementation with placebo showed that the supplementation significantly improved the rectus femoris muscle area and quadriceps muscle strength at 2 years after TKA, although clinical outcomes such as knee pain, 6-meter walk, daily living activities, and range of motion were not significantly different 20 . A separate RCT comparing vitamin D 3 supplementation before TKA with placebo did not demonstrate significant improvements in function, the TUG test, or complications up to 6 weeks after the surgical procedure 21 .…”
Section: Primary Tka Perioperative Carementioning
confidence: 99%